SELULOSA NANOSERAT TANDAN SAWIT SEBAGAI MATRIKS FILM INDIKATOR ALAMI KESEGARAN PANGAN - Yusnaidar Yusnaidar; Wilda Syahri; I Putu Mahendra (Journal of Science and Applicative Technology, 2023)
The food freshness is one trending topic that currently studied to reduce the number of food waste. The development of food freshness film indicator is one technique that can be utilized to resolve the high number of food waste. The objective of this study was to evaluate the ability of cellulose nanofiber film that had been integrated with anthocyanine as the food freshness film indicator. Cellulose nanofiber was obtained from empty fruit bunch of palm oil that had been dried, cut, and milled into fine powder. The initial step of this preparation was bleaching process using NaOCl/NH3 and H2O2/NH3. After bleaching process, cellulose fiber was oxidized using TEMPO/NaOCl/NaBr at pH 10 for 6 h. The TEMPO-oxidized cellulose fiber was then transferred into high pressure-homogenizer for 6-cycles at 800 bar of pressure. The cellulose nanofiber was obtained as hydrated fiber (gel-like) and then combined with anthocyanine obtaining from red cabbage extract, the film was casted on the acrylic plate. The film indicator of cellulose nanofiber was analyzed to determine the characteristic of film, i.e., color stability depending on pH, morphology, mechanical properties, and color response of film on the food freshness. The film of cellulose nanofiber that integrated with anthocyanin extract has the good sensitiveness to test the food freshness at 4oC. The color change produced by this indicator film is quite significant and has a different color at each pH value.